2022
DOI: 10.15252/embj.2022110928
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the human segmentation clock in somitoids in vitro

Abstract: Each vertebrate species appears to have a unique timing mechanism for forming somites along the vertebral column, and the process in human remains poorly understood at the molecular level due to technical and ethical limitations. Here, we report the reconstitution of human segmentation clock by direct reprogramming. We first reprogrammed human urine epithelial cells to a presomitic mesoderm (PSM) state capable of long-term self-renewal and formation of somitoids with an anterior-to-posterior axis. By inserting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…This mechanism assumes a significant role in biological processes. For example, during human segmentation development, antagonistic gene pairs associated with WNT, FGF, and Notch pathways collectively contribute to the formation of paraxial mesoderm segmentation and the establishment of segmental clock [25, 26]. Signals within this pathway are crucial for maintaining an overall regulatory trend, which holds significant biological implications in terms of monotonic modulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism assumes a significant role in biological processes. For example, during human segmentation development, antagonistic gene pairs associated with WNT, FGF, and Notch pathways collectively contribute to the formation of paraxial mesoderm segmentation and the establishment of segmental clock [25, 26]. Signals within this pathway are crucial for maintaining an overall regulatory trend, which holds significant biological implications in terms of monotonic modulation.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of body segments along with the anterior-posterior axis is facilitated by concentration gradients of growth factors. The induced selfsustaining oscillations also necessitates the coordination between global signaling and local states [24][25][26]. The hidden mechanism, known as monotonicity, refers to the well-organized set of positive and negative consistent regulations that form sustaining or oscillating signal patterns [27].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the in vivo development of presomitic mesoderm [ 9 , 11 , 52 ], UiPSM cells are capable of differentiating into skeletal myocytes, osteoblasts, and chondroblasts in vitro. Our prior work has shown that UiPSM cells, reprogrammed from urinary cells (UCs) and exiting the pluripotent state, retain somatic stemness, thereby mitigating the risk of tumorigenesis [ 10 ]. This suggested the potential of UiPSM cells to serve as a developmental model for musculoskeletal research.…”
Section: Discussionmentioning
confidence: 99%
“…Refer to the paper [ 10 ]. Human urine derived epithelioid cells were electrical transduced unintegrated plasmids (pEP4EO2SET2K and pCEP4-miR-302–367 cluster) using Amaxa™ Basic Nucleofector™ Kit (Lonza, VPI-1005), then cultured 7–12 days in the induction medium (IM: advanced DMEM/F12 (Gibco, 12,634–010) supplemented with 3 µM CHIR99021 (Synthesized in GIBH), 10 ng/ml bFGF (PeproTech P09038), 5 ng/ml EGF (R&D systems, 236-EG) and 5 µM EPZ5676 (Selleck Chemicals S7062)), changed the medium every 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation